ANALISIS KEMAMPUAN GURU DALAM MENYUSUN PERENCANAAN PEMBELAJARAN KURIKULUM 2013 DI SEKOLAH DASAR - Dea Mustika; Nurhayati Nurhayati; Nurhizrah Gistituati; Alwen Bentri (el-Ibtidaiy:Journal of Primary Education, 2021)
This study aims to describe the ability of teachers in preparing the 2013 curriculum learning plans in elementary schools. This type of research is descriptive qualitative research with the research subject of class teachers and school principals. Data collection techniques in the form of observation, interviews and document review. The data analysis technique uses the Milles and Huberman model which consists of three stages, namely the data reduction stage, the data presentation stage and the conclusion drawing stage. The results showed that the teacher had prepared a 2013 curriculum lesson plan by developing a syllabus and lesson plans. In addition, the teacher periodically also makes revisions to the lesson plans that have been made, only the fact that in the preparation of learning plans sometimes teachers do not go through the stages as directed in the 2013 curriculum. Needs to be done an evaluation so that the quality of the lesson plans that teachers produce can be even better.